EXAMINING EDUCATORS’ STRATEGIES IN TEACHING ENGLISH FOR SPECIFIC PURPOSES: A CASE ANALYSIS - Devinka Nandya Putri Kirani; Wiwiet Eva Savitri (Yavana Bhasha : Journal of English Language Education, 2023)
The effectiveness of English language teaching in the classroom can be influenced by a multitude of factors, and among these, the teaching style employed by the teacher is a critical determinant that can significantly impact the success of the learning activities. This study aims to investigate the types of teaching strategies employed by English teachers in teaching English in vocational high schools, specifically under the implementation of the Merdeka Curriculum launched by the Indonesian Ministry of Education. A qualitative research approach has been adopted, and data collection will be done through two main techniques: classroom observation and interviews. The results showed that both teachers implemented lecturing and small group discussions as their primary teaching strategies. The study also revealed the need for English lessons to be more specific to a topic that is closely related to students' majors, as highlighted by previous research. Moreover, the study revealed that different learning topics necessitate different teaching strategies, and using multiple strategies can enhance learning outcomes.